I am confused with the wedging operations of Lie algebra valued differential forms. Especially, for instance, I have some problems with the Chern-Simons 3-form

$$A \wedge dA + \frac{2}{3}A \wedge A \wedge A,$$

where $A$ is a **Lie algebra valued** 1-form. My question is "how is the last term $A \wedge A \wedge A$ defined?"

As far as I know, a lot of sources (e.g. Wedge Product of Lie Algebra Valued One-Form, http://en.wikipedia.org/wiki/Lie_algebra-valued_differential_form) define the wedge of Lie algebra valued 1-forms as follows.

$$[\omega \wedge \eta](X_1,\dots,X_{p+q}) := \text{(coefficient)}\times \sum_{\sigma \in S_{p+q}} \text{sgn}(\sigma) [\omega(X_{\sigma(1)},\dots,X_{\sigma(p)}),\eta(X_{\sigma(p+1)},\dots,X_{\sigma(p+q)})],$$

where $\omega$ and $\eta$ are Lie algebra valued $p$-form and $q$-form, respectively. The coefficient differs by authors. Other people utilises local description (e.g. https://math.stackexchange.com/questions/315235/reference-for-lie-algebra-valued-differential-forms, and also in the Wikipedia)

$$[\omega \wedge \eta] = [\omega^a \otimes T^a, \eta^b\otimes T^b] := \omega^a \wedge \eta^b \otimes [T^a,T^b],$$

where $T^c (c=1,\dots,\dim \mathfrak{g})$ are generators of the Lie algebra $\mathfrak{g}$, and the implicit sums understood.

These definitions, as the notations suggest, force you to take Lie bracket explicitly. Therefore it is obvious that wedged one $[\omega\wedge\eta]$ is **Lie algebra valued** $(p+q)$-form.

Then what about wedged ones **without brackets**, such as $A\wedge A, A\wedge A \wedge A$?

I can show that $A \wedge A$ is equivalent to $[A \wedge A]$ up to coefficient, using either matrix representation, considering $\mathfrak{g}=\mathfrak{gl}(n)$, or universal enveloping algebra. The basic idea is

$$A \wedge A = (A^a \otimes T^a) \wedge (A^b \otimes T^b) = (A^a \wedge A^b) T^a T^b.$$

This time, by graded commutation relation, the multiplication of generators can be converted to commutators. This seems ok. Then what about $A\wedge A \wedge A$? I could not convert it to an expression only using commutators of generators...

So, what I did was calculating $[A \wedge [A \wedge A]]$, which gave **zero**. I am totally confused at this stage. Could you point out some pieces that I possibly keep missing??